2017
DOI: 10.1002/jor.23287
|View full text |Cite
|
Sign up to set email alerts
|

Dual growth factor delivery from biofunctionalized allografts: Sequential VEGF and BMP-2 release to stimulate allograft remodeling

Abstract: Autografts have been shown to stimulate osteogenesis, osteoclastogenesis, and angiogenesis, and subsequent rapid graft incorporation. Large structural allografts, however, suffer from limited new bone formation and remodeling, both of which are directly associated with clinical failure due to non-unions, late graft fractures, and infections, making it a priority to improve large structural allograft healing. We have previously shown the osteogenic ability of a polymer-coated allograft that delivers bone morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Considering this concept, several studies have focused their efforts in the design of sequential or dual delivery systems for both vascular endothelial growth factor (VEGF) and the bone morphogenetic protein-2 (BMP-2) [151, 152]. The combination of both growth factors enhances the chances of bone regeneration compared to scaffold loaded with a single growth factor.…”
Section: Endogenous Cell Recruitment Strategies For Bone Regenerationmentioning
confidence: 99%
“…Considering this concept, several studies have focused their efforts in the design of sequential or dual delivery systems for both vascular endothelial growth factor (VEGF) and the bone morphogenetic protein-2 (BMP-2) [151, 152]. The combination of both growth factors enhances the chances of bone regeneration compared to scaffold loaded with a single growth factor.…”
Section: Endogenous Cell Recruitment Strategies For Bone Regenerationmentioning
confidence: 99%
“…In our previous work we developed a polymeric system that can deliver VEGF and BMP‐2 simultaneously from structural cortical allografts, with the VEGF eluting earlier than the BMP‐2 . We have confirmed the bioactivity of released BMP‐2 both in vitro and in vivo and have demonstrated that released VEGF can stimulate enhanced osteoclastogenesis when combined with RANK ligand, in vitro .…”
Section: Introductionmentioning
confidence: 77%
“…In our previous work we developed a polymeric system that can deliver VEGF and BMP‐2 simultaneously from structural cortical allografts, with the VEGF eluting earlier than the BMP‐2 . We have confirmed the bioactivity of released BMP‐2 both in vitro and in vivo and have demonstrated that released VEGF can stimulate enhanced osteoclastogenesis when combined with RANK ligand, in vitro . In vivo evaluation of BMP‐2 delivery from coated allografts showed organized bone formation along the length of the defect, fully encapsulating the coated allograft but the BMP‐2 concentration delivered in those studies was high.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations